Guiding management of therapy in prostate cancer: time to switch from conventional imaging to PSMA PET?. (September 2019) - Alipour, Ramin; Azad, Arun; Hofman, Michael S.
Radiolabelled small molecules for imaging prostate cancer have rapidly emerged over the last few years with gallium-68-labelled prostate-specific-membrane-antigen-11 ( 68 Ga-PSMA11), the most widely used. However, the current evidence-based guidelines for management of prostate cancer were established using computed tomography (CT), magnetic resonance imaging (MRI) and bone scan, despite their limitations. Prostate-specific-membrane antigen (PSMA) positron-emission tomography (PET)/CT, however, has higher sensitivity and specificity and can lead to both upstaging and downstaging and subsequent changes in management of prostate cancer. The literature for PSMA PET/CT is mostly in the setting of biochemical recurrence and primary staging of intermediate-to-high-risk prostate cancer. Preliminary studies also suggest that there may be a role in nonmetastatic castrate-resistant prostate cancer (nmCRPC) and possibly response to therapy. Despite high sensitivity and specificity, PSMA PET/CT as a single modality for staging advanced prostate cancer is suboptimal, given the low PSMA expression in this subgroup and the complementary role of fluorodeoxyglucose (FDG) PET/CT is required. This is also true in early-stage prostate adenocarcinoma with neuroendocrine differentiation or small-/large-cell neuroendocrine tumours of the prostate. Lack of a globally accepted standardized reporting system for PSMA PET/CT is a current limitation. This is essential to pave the way to incorporating this invaluable molecular imaging modality in clinical trials to assess its impact on outcome, particularly when upstaging or downstaging conventionally imaged disease. This would then lead to recognition by healthcare providers, incorporation into guidelines for management of prostate cancer and routine use in clinical practice.